EIAV encodes an accessory protein that antagonizes the host restriction factor equine tetherin - Bowen Bai; Xiangmin Zhang; Mengmeng Zhang; Weiwei Ma; Jiwei Li; Haili Zhang; Lei Na; Xing Guo; Yuezhi Lin; Xue-Feng Wang; Xiaojun Wang (Proceedings of the National Academy of Sciences, 2025)
Equine infectious anemia virus (EIAV) is an important model for the study of pathogenesis in lentiviruses. Studies of viral genome organization and replication mechanisms are fundamental to the understanding of virus pathogenicity. In this study, we identified an unique transcript from EIAV in vivo and in vitro by Sanger sequencing and Northern blotting. The transcript contains a complete open reading frame and has length 369 nt. We named the protein encoded by this transcript S4 and demonstrated its expression in EIAV-infected cells. An S4-deficient EIAV infectious clone displayed obviously impaired virion release and attenuated virus replication in vitro, demonstrating that S4 plays a role in the release step of EIAV. The host restriction factor tetherin has broad-spectrum antiviral activity and prevents the release of a wide range of enveloped viruses, including lentiviruses. Here, we demonstrated that S4 enhances the release of the EIAV-like particle by counteracting the equine tetherin (eqTHN). S4 interacts with the eqTHN and sequesters it within intracellular membrane compartments, attenuating eqTHN expression on the cell surface and thereby disrupting its antiviral activity. Further investigation revealed that S4 retains eqTHN in the endoplasmic reticulum and trans-Golgi network through impacting its anterograde transport to the cell surface and may interfere with the posttranslational modification of this membrane protein. Collectively, our findings uncover an accessory protein, S4, of EIAV and reveal its ability to promote virion release by antagonizing the antiviral activity of the host restriction factor tetherin.